Study of flavor dependence of the baryon-to-meson ratio in proton-proton collisions at √s=13 TeV - Acharya, Shreyasi; Angelov, Venelin; Berdnikova, Anastasia; Bergmann, Luisa; Bórquez Cárcamo, Andrés G.; Crkovská, Jana; Danisch, Meike; Feuillard, Victor; Fokin, Ilya D.; Glässel, Peter; Kroesen, Martin; Nath, Abhishek; et al. (Physical review, 2023)
The production cross sections of D0 and Λ+c hadrons originating from beauty-hadron decays (i.e., nonprompt) were measured for the first time at midrapidity (|𝑦|<0.5) by the ALICE Collaboration in proton-proton collisions at a center-of-mass energy √𝑠=13 TeV. They are described within uncertainties by perturbative QCD calculations employing the fragmentation fractions of beauty quarks to baryons measured at forward rapidity by the LHCb Collaboration. The b⁢¯b production cross section per unit of rapidity at midrapidity, estimated from these measurements, is d⁢𝜎b⁢¯b/d⁢𝑦||𝑦|<0.5=83.1±3.5⁢(stat)±5.4⁢(syst)+12.3−3.2⁢(extrap) μ⁢b. The baryon-to-meson ratios are computed to investigate the hadronization mechanism of beauty quarks. The nonprompt Λ+c/D0 production ratio has a similar trend to the one measured for the promptly produced charmed particles and to the p/𝜋+ and Λ/K0S ratios, suggesting a similar baryon-formation mechanism among light, strange, charm, and beauty hadrons. The 𝑝T -integrated nonprompt Λ+c/D0 ratio is found to be significantly higher than the one measured in e+⁢e− collisions.